The association between pulmonary function test and anthropometric measurements using bioelectric impidence analysis in adolescents - Surve, Rahul R.; Dase, Rajesh K. (International Journal Of Community Medicine And Public Health, 2018)
Background: The development of pulmonary functions and growth of physical parameters i.e. height and weight are coexistent. These physical parameters are further affected by nutrition and physical activities of children. The aim of present study was to find correlation between pulmonary function test and anthropometric measurements using bioelectric impedance analysis in adolescence. Methods: A cross sectional observational study conducted at Sanskar Madhmik Vidhylay, Mayur Park, Aurangabad during July to December 2017. Adolescent between the age group between 11 to 18 years were enrolled in present study. Results: Out of 138 total students 80 (57.97%) were male and 58 (42.02%) female. As per person correlation test analysis weight, height, Hip circumference and body surface area are found to be positively correlated to FVC, FEV1, PEFR and FEF25-75. As per person correlation test analysis total body fat, trunk subcutaneous fat and whole body subcutaneous fat are found to be negatively correlated to FVC, FEV1, PEFR and FEF25-75. Muscle mass and basal metabolic rate are found to be positively correlated to FVC, FEV1, PEFR and FEF25-75. Conclusions: Total body fat, trunk subcutaneous fat and whole body subcutaneous fat are negatively correlated with pulmonary function test. The body fat percentage had a stronger correlation than BMI, thus suggesting that body fat percentage was a major determinant of the reduced pulmonary functions in both sexes.